Development of sequencing methods to illuminate the epitranscriptome - Heng, Joel Jia Wei (Nanyang Technological University, 2025)
RNA modifications are chemical marks which expand genetic vocabulary beyond the canonical A, G, C, and T/U. The first RNA modification was discovered in 1957. While over 160 varieties of RNA modifications have been recorded since, the discovery that certain RNA modifications are reversible and can be erased sparked new enthusiasm in the research area. The improvements in sequencing technologies over the years also catalysed this renewed interest. Advancements in high-throughput sequencing have reduced costs and improved the accessibility of studies on the Epitranscriptome – RNA modifications and their associated RNA-binding proteins. The advent of nanopore sequencing further stoked the field’s interest with the introduction of direct RNA sequencing (DRS) which can sequence RNAs in their native state. DRS can be performed without reverse transcription, which typically erases the chemical modification of interest, and amplification, which potentially introduces biases. While showing much promise with direct RNA modification detection, DRS inherently contains a high noise background and requires more development.